2016
DOI: 10.1371/journal.pone.0164427
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Linked Chromosome Heterozygosity in Males of Tityus confluens (Buthidae): A Clue about the Presence of Sex Chromosomes in Scorpions

Abstract: Scorpions of the genus Tityus show holokinetic chromosomes, achiasmatic male meiosis and an absence of heteromorphic sex chromosomes, like all Buthidae. In this work, we analysed the meiotic behaviour and chromosome rearrangements of a population of the scorpion Tityus confluens, characterising the cytotypes of males, females and embryos with different cytogenetic techniques. This revealed that all the females were structural homozygotes, while all the males were structural heterozygotes for different chromoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 35 publications
2
12
0
Order By: Relevance
“…Intraspecific variability in diploid number has been recorded in 40% of the 18 karyotyped Tityus species [ 42 , 69 ]. Similar to the species investigated herein, previous studies revealed variations at the inter- and intra-population levels and attributed differences in chromosome number to fission/fusion rearrangements [ 29 , 39 , 41 , 42 , 48 ]. In specimens of T .…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…Intraspecific variability in diploid number has been recorded in 40% of the 18 karyotyped Tityus species [ 42 , 69 ]. Similar to the species investigated herein, previous studies revealed variations at the inter- and intra-population levels and attributed differences in chromosome number to fission/fusion rearrangements [ 29 , 39 , 41 , 42 , 48 ]. In specimens of T .…”
Section: Discussionsupporting
confidence: 78%
“…Studies examining specific chromosomal regions in scorpions have increased significantly in recent years [ 29 , 39 42 , 48 , 83 87 ]. Data regarding the localization of NORs and rDNA has revealed remarkable stability, particularly in Tityus species, in which more than 80% of the species presented a similar pattern, i.e., NORs/rDNA in the terminal regions of two chromosomes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations